The morphology of the circulus arteriosus cerebri in the ground squirrel (Spermophilus citellus) - Aydin, A.; Ozkan, Z. E.; Yilmaz, S.; Ilgun, R. (Czech Academy Agricultural Sciences, 2009)
In this study, the circulus arteriosus cerebri of the ground squirrel (Spermophilus citellus) was investigated. Five ground squirrels were used as subjects. Coloured latex was injected from the left ventriculi of the hearts of all the squirrels. When the vertebral arteries of two of the animals were ligatured, it was found that there was no internal carotid artery. After careful dissection, the circulus arteriosus cerebri (the circle of Willis) was investigated. The right and left vertebral arteries gave rise to the caudal cerebellar artery before forming the basilar artery. The basilar artery formed the caudal communicans artery that was the caudal part of the circulus arteriosus cerebri on the pontocrural groove (sulcus pontocruralis). The caudal, medial, rostral cerebellar, the common root formed by the caudal cerebral and choroid arteries, the rostral choroid, the rostral and medial cerebral arteries arose from the vertebral, basilar and caudal communicans arteries and dispersed to the cerebrum and cerebellum from caudal to cranial. The termination and the branches of the rostral cerebral artery in ground squirrels varied. It was observed that the internal carotid artery does not supply the circulus arteriosus cerebri in ground squirrels.
Keywords: morphology; circulus arteriosus cerebri; brain; ground squirrel (Spermophilus citellus)